Severe Case Of Delayed Diagnosed Of >10 Years Untreated Newborn Congenital Glaucoma: Poster Presentation - Case Report - General practitioner - Yudakusuma, Cheryll; Siahaan, Yoseph M.P. A (Majalah Oftalmologi Indonesia, 2023)
Introduction : Though cases of newborn primary congenital glaucoma (PCG) had poor prognosis, we couldn’t simply ignore that early proper diagnostic and treatment can still improves quality of one’s sight, which’s absent in this case. Presented with delayed diagnosed highly suspected case of newborn PCG, physician was compelled to make the best in condition of the already given poor prognosis to begin with. Case Illustration : A 13 years old female patient came to eye clinic with a very disturbing chronic condition of visual loss. Accompanied by her family, who also claimed had witnessed both the patient’s eyes appeared whitish since birth. Eye examination revealed visual acuity of 1/~ for right eye and no light perception for left eye, along with significant signs of buphthalmos, epiphora, nystagmus, megalocornea (diameter of 9x14mm right eye and 9x13.3mm left eye), cloudy cornea, leukocoria, and Schiotz tonometry of 60-100mmHg in both eyes. Patient then received oral Acetazolamide, Levofloxacin eye drop, and Timolol Maleate 0,5% eye drop; then advised to return for one week evaluation also to bring her siblings to be subjected to glaucoma screening. Discussion : The decision to perform surgical intervention in cases of newborn PCG commonly require further thoughts. This case immediately shifted our focus towards palliative care of the patient whilst continuing monitoring IOP, as glaucoma surgery possessed a more menacing risk to be performed this patient. Conclusion : All cases of pediatric glaucoma require a life time of comprehensive management that requires heedfulness especially from caregivers as it is a very challenging disease.